Das Konzept der Ökologie in der amerikanischen Geographie - Fuchs, Gerhard (ERDKUNDE, 1967)
In recent times, interest in the ecological thought pattern has been revived in German geography by chorological research (Troll/Paffen) as well as by studies in social geography. There is, however, only little knowledge of the fact that a special body of ecological theory was developed in American geography between 1900 and 1930, thus anticipating the spread of ecological thought in European geography. This period is generally neglected in the presentation of the history of geography and mostly restricted to the name of H. H. Barrows, but as a whole deserves the merit of first introducing a certain amount of ecological thought into geographic theory. Theoretical argument during the phase when geography defined itself as 'a science of relationships' centred in the quest for an organizing concept of the newly developed branch of human geography, and later on for geography in general. Human geography, especially after the decline of geographical determinism, had come to emphasize the reciprocal relationships between man (culture) and physical environment, a concept showing obvious analogy to that of contemporary ecologists. Based on this coincidence of concepts, geographers in general looked for models in ecology. This exclusive derivation of thought patterns from the biological sciences originated in the naturalistic learning of the early American geographers as well as in their Darwinistic understanding of man and thus led to a general naturalistic emphasis. In geographic theory, the first one to include ecological thought was W. M. Davis in connection with his concept of ontography. Discussion was carried on by A. P. Brigham; Ch. R. Dryer then came to identify human geography with ecology in his address before the Association of American Geographers, also introducing again the term “human ecology. The position of H. H. Barrows (geography = human ecology) is widely known but in the light of the foregoing development it can no longer be considered as isolated as most geographers regard it. The rise of cultural geography showed the limits for ecological thought in geography concerning man. C. O. Sauer, in his attempt to close the discussion on that particular subject, simply came to substitute his theory of cultural morphology for human ecology. M. Aurousseau, emphasizing the community-concept, was near to the socio-ecological theory of the Chicago school but remained without connection or influence, and D. S. Whittlesey's introduction of the sequent occupance study in analogy to plant succession quickly developed into a general genetic treatment of the cultural landscape. - A thorough analysis of the key terms of geographic theory of this time will testify to the special ecological aspect of American geography in the first quarter of this century.